To explore the importance of brand to Chinese product under the international environment - HOU, Shuhao (2013)
Brand is the sum of all tangible and intangible attributes of a product and branding is the core part of marketing which segment the market and determine the target customers of the company. Branding today is more about corporate branding which link the internal stakeholders and external stakeholders. That would allow firms to create a strong brand through integrated operation in the corporate level. Chinese manufacturing industry was criticized as “good manufacturing but no brand” and “advertising as branding”, it is valuable to investigate what is the current situation in the world second largest economy and what is the future of “made in China”. In order to analyze what is the current situation of Chinese brand and explore the feasible strategy to the industry, the author proposed a research that looks into the Chinese manufacturing industry in order to explore what are the connotation of “made in China” and where is the way for the transition economy just like China. This study mainly employs qualitative research which assisted by quantitative methods. In order to meet the research objectives, a specifically designed questionnaire accompany with several management interviews aimed at collecting primary data. The quantitative methods such as descriptive analysis, means and regression are employed to analysis the data. Through investigate the primary data; it is an urgent task for Chinese firms to use their own brand to compete in the international marketplace. To improve the quality and shorter the lead time could add more value to Chinese products (brands), and service is the main constraint for Chinese firm to create brand in the oversea market. For the further improvement, some feasible strategies are recommended from different level of strategies in order to deliver high quality product with secure time and good services. Firstly, the M&A is recommended as corporate level strategy which aims to acquire the advanced management skills, R&D assets and oversea market distribution channels. Secondly, invest on R&D and developing the own distribution channels are recommend as business level strategy. Thirdly, to implement international standard quality control system is recommended as operational level strategy.